Identification of Behavior patterns related to lifestyle in Gorgan university students - morteza mansourian; AZIZ REZAPOOR; HADI RAHIMZADE; ZAINAB SHAFIEYAN; ABDOLRAHMAN CHARKAZI; HAMID ASAYESH; MOSTAFA QORBANI (Iranian Association of Health Education and Health Promotion, 2014)
Background & Objective: person lifestyle is determined with behavior patterns and affects individual and social health. The aim of this study was Identification of lifestyle in Gorgan universities students in 2008. Material & Method: This study was cross - sectional study that 800 students of Gorgan University of Medical Science, Agriculture sciences and natural resource, Payam E Nor and Azad university were selected via systematic sampling. The data collection were using by a questionnaire that includes demographic questions and lifestyle questionnaire.After the data collection analysis performed by SPSS 16 software and Chi square test. A P- value less than 0.05 considered as statistically significant. Results: The mean age was 22.43, 22/1 % were married, 65.5 % were native of Golestan, BMI mean was 24.1% and 21.8 % have smoke almost and sometimes, lifestyle score was categorized in 4 groups, 24.1% had weak, 29.6% moderate, 22.9% good and 23.4 % excellent lifestyle. The relation between lifestyle and gender, degree of education, family income, father educational level, mother job, being native of Golestan and university were significant (p-value <0.05). The lifestyle status of medical science students were better than other groups and female students had better lifestyle compare to male students. Conclusion: This results shows that more than half of the students have weak and moderate lifestyle status, that needs to planning for changing students behaviors and lifestyle status, particularly in physical activity, nutrition and stress management.